Patients’ perception of using telehealth for type 2 diabetes management: a phenomenological study - Greenfield,G; Lee,P; Pappas,Y (BMC Health Services Research, 2018)
Background:There is a growing body of evidence that supports the uses of telehealth to monitor and manage people with diabetes at a distance. Despite this, the uptake of telehealth has been low. The objective of this study is to explore patients’ perceptions of using telehealth for type 2 diabetes management.Methods:Semi-structured interviews were undertaken with 10 patients from the NHS Newham area in London, UK. Data were collected using recorded semi-structured interviews. The interviews were transcribed verbatim and the analysis was guided by the phenomenological analysis approach.Results:We identified three main themes for facilitating positive patient experience or acceptance of telehealth and these included: technology consideration, service perceptions and empowerment. All patients asserted that they were pleased with the technology and many also proclaimed that they could not see themselves being without it. Moreover, very few negative views were reported with respect to the use of telehealth.Conclusion:The patients’ perceived telehealth as a potential to enhance their quality of life, allow them to live independently at home as well as help them take and be in more control over their own health state. The findings of this study therefore supports the use of telehealth for the routine care of people with type 2 diabetes. However, one must interpret the results with caution due to limitations identified in the sample.